Geoprocessamento da coinfecção tuberculose/HIV drogarresistente no Estado do Ceará - Santos, Vanessa da Frota (2018)
The objective of this study was to analyze the spatial distribution of cases of drug-resistant Tuberculosis / HIV co-infection in adults in the State of Ceará and its correlation with social, economic and health indicators. An ecological study was carried out that had as unit of study the municipalities of the state of Ceará and the neighborhoods of the capital, Fortaleza. We analyzed 49 cases of drug-resistant Tuberculosis / HIV coinfection, reported during the period from August 2011 to August 2018. The data were collected in the Tuberculosis Special Treatment Information System, in the Aggravation and Notification Information System and in the Brazilian Institute of Geography and Statistics. The epidemiological profile of the patients was traced by means of descriptive analysis, using absolute and relative frequencies. For the data analysis of the association between the socio-demographic and epidemiological characteristics of the co-infected, Fisher's exact test was applied. Pearson correlation analysis was carried out between the cases and the socioeconomic indicators. Spatial analysis was performed through exploratory analysis and spatial autocorrelation by the Moran Global Index. It was verified that there was an increase in the number of cases reported in recent years, especially in 2017 (24.5%) and occurrences occurred in 13 municipalities of Ceará, and the prevalence of cases (63.8%) occurred in Fortaleza. The neighborhoods that presented the highest percentage of cases were Barra do Ceará (16.2%) and Bonsucesso (13%) and the Moran index presented positive spatial association (I = 0.036). The percentage of people from other races that had other types of drug-resistant tuberculosis classification was higher than the percentage of brown people (p = 0.04) and the percentage of people with two or more comorbidities and pulmonary clinical form was higher than the percentage of those with only one comorbidity and clinical pulmonary form (p = 0.01). The neighborhoods with the best socioeconomic conditions are to the north and northeast of the city of Fortaleza, and the neighborhoods with the highest proportion of households in the poverty line are located in the peripheries. There was a prevalence of cases in neighborhoods with a mean of 3.44 - 3.61 residents, in households with 1 to 3 bathrooms for exclusive use and that have owners with average income between 429.02 and 1181.32 reais. In view of the above, it was identified that the majority of cases of drug-resistant tuberculosis / HIV coinfected are located in Fortaleza, in socially disadvantaged regions, urging the need for interventions directed to the social context in which this population is inserted.